Regulation of estrogen signaling and breast cancer proliferation by an ubiquitin ligase TRIM56 - Xue, Min (Oncogenesis, 2019)
Breast cancer ranks no. 1 in women cancer worldwide, while 60–70% are estrogen receptor alpha positive. The estrogen selective modulators, such as tamoxifen, become the effective drugs for controlling ER alpha breast cancer progression. However, tamoxifen resistance will develop during long-time treatment and cancer progression. Thus, further understanding of ER alpha signaling becomes necessary for the improvement of breast cancer therapy. Here, we identify TRIM56 as a novel regulatory factor in ER alpha signaling. TRIM56 expression is positively correlated with ER alpha and PR in breast cancer samples and is related to poor prognosis in endocrine therapy patients. TRIM56 depletion significantly decreases ER alpha signaling activity and ER-alpha-positive breast cancer proliferation in vitro and in vivo. TRIM56 associates with AF1 domain of ER alpha via its WD40 domain in the cytoplasm. TRIM56 prolongs ER alpha protein stability, possibly through targeting ER alpha K63-linked ubiquitination. In conclusion, our study reveals an interesting posttranslational mechanism between TRIM56 and ER alpha in breast cancer progression. Targeting TRIM56 could be a promising approach for ER-alpha-positive breast cancer.